A leitura dos enunciados dos problemas matemáticos e as estratégias para a resolução por alunos do 9º ano do ensino fundamental - Leite, Lidiane Camilo Sossolote [UNESP] (2014)
The purpose of this dissertation was to understand how to read the statements of mathematics problems occur, with a view to its resolution, by 9th grade students of elementary school. The school investigated is in the town of Garça/SP and was selected from the results of the Evaluation of Educational Achievement System (SARESP) 2012, by the best performance for the subjects tested, and the class, due to better school performance in the 1st quarter of 2013. The research was based on ethnographic type questionnaire, observation, interviews and document analysis, recorded in field notes and audio recordings. It is expected that this work will contribute to a better understanding of the relationships established between the student to read the statement of mathematical problem, and in consequence of it, the possibilities for settlement, and that it can furthermore cause reflections on pedagogical practice, so that the teaching of mathematics is meaningful to the student, he then appropriates the scientific concepts and become the subject of social transformation.